Co-Creating Authentic Sacred Therapeutic Space: A Spiritually Sensitive Framework for Counselling Children - Heather M. Boynton; Christie Mellan (Religions, 2021)
Social work values client-centered holistic approaches of care, yet there is a lack of approaches addressing spirituality in counselling with children. Children’s spirituality and conceptualization have been disenfranchised. Children’s spiritual experiences, ways of knowing and perceptions are important to attend to when supporting them through an impactful life event such as trauma, grief, or loss (TGL). Parents may not fully understand or have the capacity to attend to their child’s spirituality. Counsellors appear to lack knowledge and training to attend to the spiritual needs and capacities of children. This article offers some research findings of children’s spirituality deemed to be vital for healing from TGL and counselling. It provides an understanding of some of the constructs and isolating processes described by children, parents and counsellors related to children’s spirituality in TGL. It also will present a spiritually sensitive framework specifically attuned to the spiritual dimension and creating spaces of safety and hope when working with children. The implications of not addressing the critical spiritual dimensions in practice for children are discussed, and recommendations for continued research and training for further theoretical development and future social work practice are offered.